Feminist Value and Openness to Interfaith Marriage: A Study of Environmental Influences on Gen-Z Women - Yasin, Ahmad Alamuddin; Rahman, Osamah Naufal; Ramadhan, Fikri Barkah (Universitas Islam Negeri Alauddin Makassar, 2026)
Generation Z or Gen-Z is known to be more open to social issues that were previously considered taboo, one of which is interfaith marriage. Amidst the tug-of-war between religious norms that tend to be conservative and digital culture that is increasingly liberal, an important question arises: to what extent do feminist values influence Gen-Z women's openness to interfaith marriage? This study aims to analyse the influence of feminist values on Gen-Z women's openness to interfaith marriage. The method used is a quantitative predictive method with a predictive modelling approach. The research sample consists of Gen-Z women who are active in gender and diversity discourse, selected using purposive sampling techniques. Data collection was conducted through a Likert scale-based questionnaire distributed online using Google Forms. The results showed that of the 222 Gen Z female respondents, the majority were born between 2003 and 2007, representing 68.46% of the sample. This represents the younger generation in their late teens to early adulthood, who tend to be open-minded and progressive. Bootstrap analysis with 5000 samples revealed that feminist values had a positive and significant effect on Gen-Z women's openness to interfaith marriage (β = 0.644; p < 0.001). This means that the higher the internalisation of feminist values, the greater their openness to interfaith marriage, reflecting this generation's inclusive attitude towards diversity in a multicultural society.